Effect of JNK inhibitor SP600125 on hair cell regeneration in zebrafish (Danio rerio) larvae - He, Yingzi (Oncotarget, 2016)
The c-Jun amino-terminal kinase (JNK) proteins are a subgroup of the mitogen-activated protein kinase family. They play a complex role in cell proliferation, survival, and apoptosis. Here, we report a novel role of JNK signalling in hair cell regeneration. We eliminated hair cells of 5-day post-fertilization zebrafish larvae using neomycin followed by JNK inhibition with SP600125. JNK inhibition strongly decreased the number of regenerated hair cells in response to neomycin damage. These changes were associated with reduced proliferation. JNK inhibition also increased cleaved caspase-3 activity and induced apoptosis in regenerating neuromasts. Finally, JNK inhibition with SP600125 decreased the expression of genes related to Wnt. Over-activation of the Wnt signalling pathway partly rescued the hair cell regeneration defects induced by JNK inhibition. Together, our findings provide novel insights into the function of JNK and show that JNK inhibition blocks hair cell regeneration by controlling the Wnt signalling pathway.